Yeast water channels: an overview of orthodox aquaporins - Soveral, Graça (2011)
The final version of record is available at http://www.biolcell.org/boc/103/boc1030035.htm. A versão final do registo está disponível em http://www.biolcell.org/boc/103/boc1030035.htm.